Barriers to HIV testing among male clients of female sex workers in Indonesia - Fauk, Nelsensius Klau (Int J Equity Health, 2018)
BACKGROUND: Frequent engagement of men in sexual encounters with female sex workers (FSWs) without using condoms places them at a high risk for HIV infection. HIV testing has been noted to be among important strategies to prevent HIV transmission and acquisition. However, it is known that not all men willingly undertake an HIV test as a way to prevent HIV transmission and/or acquisition. This study aimed to identify barriers to accessing HIV testing services among men who are clients of FSWs (clients) in Belu and Malaka districts, Indonesia. METHODS: A qualitative inquiry employing face to face open ended interviews was conducted from January to April 2017. The participants (n = 42) were clients of FSWs recruited using purposive and snowball sampling techniques. Data were analysed using a qualitative data analysis framework. RESULTS: Findings indicated three main barriers of accessing HIV testing services by clients. These included: (1) personal barriers (lack of knowledge of HIV/AIDS and HIV testing availability, and unwillingness to undergo HIV testing due to low self-perceived risk of HIV and fear of the test result); (2) health care service provision barriers (lack of trust in health professionals and limited availability of medication including antiretroviral (ARV)); and (3) social barriers (stigma and discrimination, and the lack of social supports). CONCLUSIONS: These findings indicated multilevelled barriers to accessing HIV testing services among participants, who are known to be among key population groups in HIV care. Actions to improve HIV/AIDS-related health services accessibility are required. The dissemination of the knowledge and information on HIV/AIDS and improved available of HIV/AIDS-related services are necessary actions to improve the personal levelled barriers. System wide barriers will need improved practices and health policies to provide patients friendly and accessible services. The societal levelled barriers will need a more broad societal approach including raising awareness in the community and enhanced discussions about HIV/AIDS issues in order to normalise HIV in the society.